Sandy Soils Stabilization Using Calcite Microbial Deposition - Anis Saffari; Mohammad Sharifipour; Jahangir Khazaiie; Mojtaba Taran (مدل‌سازی پیشرفته در مهندسی عمران)
Today, the need to implement construction projects in the vicinity of rivers and sea coasts is inevitable. On the other hand, the soils of these areas generally have problems such as low bearing capacity or prone to liquefaction. The need to improve these soils in order to implement huge projects such as those on the southern shores of the Persian Gulf of the Oman Sea is a necessary and inevitable thing. Considering the extent of the beaches and the need for construction projects in these areas, inventing an optimal method to stabilize them can provide a solution for the optimal use of coastal lands adjacent to rivers and seas. Among soil stabilization methods, microbial calcite precipitation (MICP) method is a new and emerging method that uses microorganisms in soil and chemical processes and as a result of producing calcite sediment, it provides the possibility of increasing shear strength, shear modulus, and also reducing soil permeability. In this research, the effects of this method on Babolsar beach sand have been investigated. For this purpose, by conducting direct shear tests and measuring shear wave velocity in non-cemented and cemented samples, the process of improving shear strength and increasing shear modulus was investigated by measuring shear wave velocity in samples prepared from Babolsar sand. Evaluation the results shows that the microbial calcite precipitation (MICP) method is effective and has caused a relative increase of two to three times in the shear strength and four times in the shear modulus of Babolsar sand. In the following, there is a good comparison and agreement between the obtained results and the results of other researchers.